Indigenizing Climate Policy in Canada: A Critical Examination of the Pan-Canadian Framework and the ZéN RoadMap - Reed, Graeme; Gobby, Jen; Sinclair, Rebecca; Ivey, Rachel; Matthews, H. Damon (Frontiers in Sustainable Cities, 2021)
Climate policies and plans can lead to disproportionate impacts and benefits across different kinds of communities, serving to reinforce and even exacerbate existing structural inequities and injustices. This is the case in Canada where, we argue, federal climate policy is reproducing settler-colonial relations, violating Indigenous rights and systematically excluding Indigenous people from policy making and decision-making. This article reports on a research project conducted in collaboration with the national organization Indigenous Climate Action. In this project we conducted a critical policy analysis on two climate plans in Canada: the Pan Canadian Framework on Clean Growth and Climate Change (PCF), a federal government-led, top-down plan for reducing emissions; and the Québec ZéN (zero émissions nette, or net-zero emissions) Roadmap, a province-wide, bottom-up energy transition plan developed by civil society and environmental groups in Quebec. We asked how and to what extent these policies and plans are : a) in alignment or conflict with the governments’ commitments to reconciliation and Nation to Nation relationships; b) violating or respecting inherent, treaty, constitutional and international Indigenous rights and c) centering or ignoring and erasing Indigenous perspectives, knowledge, and approaches to climate change mitigation and adaptation and resilience. In this article we present the findings from our analysis and lay out an agenda for Indigenous-led climate policy and planning.